(untitled) (Revista de Ciências Agroveterinárias, 2023)
Didactic biomodels have been used as a learning tool for physiology teaching, they are three-dimensional functional - artificial models that seek an approximation to the organisms function, and also to help its understanding. The objective of this study was to explore the student`s learning experience through the implementation of didactic biomodels in two universities located in Bogotá city, the subject was physiology in an undergraduate population of veterinary medicine for a whole academic year. This method consisted in using different tools such as structured surveys, Metacognition formats, teamwork and characterization of the models according to the biological system. Results in general were positive and indicated the value of didactic biomodels as a learning method and to knowledge acquisition, the students valued high marks in teamwork as a complement in solving problems, likewise, the models that aroused more interest were those carried out in unconventional species and the nervous system.